2016
DOI: 10.1007/s00343-016-5238-3
|View full text |Cite
|
Sign up to set email alerts
|

New record of Lobophora rosacea (Dictyotales; Phaeophyceae) from the South China Sea

Abstract: Lobophora rosacea C.W. Vieira, Payri et De Clerck is reported from the South China Sea for the fi rst time. Our specimens are very similar to L . rosacea recently described from New Caledonia, not only in morphology but also in rbcL and cox3 gene sequences. The fan-shaped thallus grows erectly, attaching to the substrate by a basal holdfast. The thallus is composed of a single layer of large medullary cells and three to four layers of cortical cells on both sides of the medulla. Mature sporophytes are detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Since then, there have been more studies using these new approaches to resolve the taxonomy and diversity of Lobophora. For example, four and 16 species have recently been described from the South China Sea (Sun et al 2017) and Bismarck Sea off Papua New Guinea (Vieira et al 2019a), respectively. However, with only one study conducted along the western Pacific coast (Sun et al 2012), such research remains geographically patchy and poorly represented at regional scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, there have been more studies using these new approaches to resolve the taxonomy and diversity of Lobophora. For example, four and 16 species have recently been described from the South China Sea (Sun et al 2017) and Bismarck Sea off Papua New Guinea (Vieira et al 2019a), respectively. However, with only one study conducted along the western Pacific coast (Sun et al 2012), such research remains geographically patchy and poorly represented at regional scales.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary study by Fong et al (2019) detected L. challengeriae C.W.Vieira in Vieira et al (2019a: 231) or Lobophora sp16 prior to formal description in Vieira et al (2019a), in samples collected from Pulau Subar Darat (1°12'53"N 103°49'55"E). Given the location of Singapore within the South China Sea and proximity to Papua New Guinea in Central Indo-Pacific, it is possible that some of the species described in Sun et al (2017) and Vieira et al (2019a) are found in Singapore. Moreover, recent studies have shown that L. variegata originated from the Caribbean Sea and is restricted to the Atlantic Ocean (Schultz et al 2015, Vieira et al 2016.…”
Section: Introductionmentioning
confidence: 99%